Impact of subject head motion on quantitative brain 15O PET and its correction by image-based registration algorithm - Matsubara, Keisuke; Ibaraki, Masanobu; Nakamura, Kazuhiro; Yamaguchi, Hiroshi; Umetsu, Atsushi; Kinoshita, Fumiko; Kinoshita, Toshibumi (Annals of nuclear medicine, 2013)
Objective Subject head motion during sequential 15 O positron emission tomography (PET) scans can result in artifacts in cerebral blood flow (CBF) and oxygen metabolism maps. However, to our knowledge, there are no systematic studies examining this issue. Herein, we investigated the effect of head motion on quantification of CBF and oxygen metabolism, and proposed an image-based motion correction method dedicated to 15 O PET study, correcting for transmission–emission mismatch and inter-scan mismatch of emission scans. Methods We analyzed 15 O PET data for patients with major arterial steno-occlusive disease ( n = 130) to determine the occurrence frequency of head motion during 15 O PET examination. Image-based motion correction without and with realignment between transmission and emission scans, termed simple and 2-step method, respectively, was applied to the cases that showed severe inter-scan motion. Results Severe inter-scan motion (>3 mm translation or >5° rotation) was observed in 27 of 520 adjacent scan pairs (5.2 %). In these cases, unrealistic values of oxygen extraction fraction (OEF) or cerebrovascular reactivity (CVR) were observed without motion correction. Motion correction eliminated these artifacts. The volume-of-interest (VOI) analysis demonstrated that the motion correction changed the OEF on the middle cerebral artery territory by 17.3 % at maximum. The inter-scan motion also affected CBV, CMRO 2 and CBF, which were improved by the motion correction. A difference of VOI values between the simple and 2-step method was also observed. Conclusions These data suggest that image-based motion correction is useful for accurate measurement of CBF and oxygen metabolism by 15 O PET.